EVALUATION OF BIOLOGICAL AND PHYSICOCHEMICAL RELATIONSHIPS AS INDICATORS OF WATER QUALITY IN TOLTÉN RIVER BASIN, ARAUCANÍA, CHILE: PRELIMINARY RESULTS - Guerrero_Jimenez, Claudia Jimena; Rabert, Claudia Lorena; Sáez-Arteaga, Alberto; Loncomán, Nicol; Torres, Geraldine; Flores, Tomás; Llanquín-Rosas, Francisco; Valenzuela, María Luisa; Moreno, Roberto (Journal of the Chilean Chemical Society, 2021)
River basins play a critical role in ecosystem services and their status regulate the associated productivity. Anthropogenic activities along with other environmental perturbation influence the vulnerability level of that important water resource, disturbing in a short time, water quality. The aim of this work is to generate an approach to Toltén basin characterization with benthonic macroinvertebrates, physicochemical and bacterial components as indicators of variation in water quality close to human populations and the sectors furthest from them, selecting for this purpose two areas (up and downstream of the basin). We used an ANOSIM two-way analysis to relate abiotic and biotic data and for diversity and biotic index (ChBMWP) we analyzed the benthic macroinvertebrate composition. A principal component analysis for environmental variables strongly separated the analyzed zones by season as the first principal component, showing a clear increase in temperature and electrical conductivity values in spring season. Meantime the pH parameter was observed with interesting variation for longitudinal gradient with incremental values in upstream area. The biotic indexes applied to the samples between seasons reflexes a similar diversity between analyzed sites in upstream with no differences showing a low diversity of macroinvertebrates. However, a significant increase was detected during spring in downstream zone. On the other hand, Pseudomonas genus increase between the most representative microbiological genera in the basin. Our results reinforce the importance not only of frequent seasonal monitoring program but also the critical role of collecting data on total transect basin length to regulate the human activities associated to basin and to protect the water quality.